Peer support for internalised stigma experienced by people with psychosis: rationale and recommendations. Issue 2 (3rd April 2018) - Pyle, Melissa; Pilling, Stephen; Machin, Karen; Allende-Cullen, Ginny; Morrison, Anthony P.
ABSTRACT: People with experience of psychosis face stigma and discrimination, which can be a significant barrier to recovery. Internalisation of public stereotypes and prejudice into an individual's self-identity is an understandable consequence of such discrimination. However, internalised stigma represents a significant barrier to recovery, resulting in a number of harmful consequences such as depression, demoralisation and loss of self-esteem. Interventions to support people with experience of psychosis who internalise stigma have demonstrated some promising results, but a recent meta-analysis did not find an overall significant effect. The current evidence base includes very few trials of peer support for internalised stigma; however, data from several trials and a recent meta-analysis show that peer support produces benefits on a number of dimensions related to internalised stigma, including empowerment, recovery and hope. In this paper, we argue that peer support is a suitable intervention for addressing internalised stigma and warrants further research. We provide a theoretical and evidence-based rationale for this argument and outlines some of the key challenges and possible solutions for future trials of peer support as an intervention for internalised stigma.